Relationship between frequency of infectious human immunodeficiency virus type 1-harboring cells and kinetics of viral replication: a simple procedure for quantitation of infectious virus-carrying cells in blood samples. - Lu, W (1992)
Statistical analysis of a limiting dilution assay (LDA) showed that the occurrence of infectious human immunodeficiency virus type 1 (HIV-1)-harboring cells in serially diluted samples of peripheral blood mononuclear cells (PBMCs) of HIV-1-seropositive patients fits the model describing a single-hit Poisson distribution. This observation led to the discovery that there is a direct correlation (r = 0.957) between the number of HIV-1-positive cells and the time when viral culture produces 1 ng of the HIV-1 p24 gag protein per ml. Frequency estimates based on this relationship were highly accurate (P less than 0.01) within the first 15 days of viral culture, which consisted of coculture of 10(6) normal PBMCs with the equivalent number of test PBMCs. This approach was less cumbersome than LDA and was sensitive enough to detect a single infectious HIV-1-harboring cell among as many as 320,000 cells. The values obtained for 57 patients agreed well with the data in the literature and showed that the frequencies of infectious cells in PBMCs reflect the advancement in the clinical stage, being 1/38,000, 1/11,000, and 1/7,000 for asymptomatic patients (Centers for Disease Control [CDC] group II/III), patients with AIDS-related complex (CDC group IVa), and patients with AIDS (CDC group IVb/c), respectively. A nearly 10-fold disparity in mean frequencies was observed when these values were correlated with the numbers of CD4-positive cells (1/9,000, 1/1,500, and 1/300, respectively, for asymptomatic patients, patients with AIDS-related complex, and patients with AIDS). The described method provides a simple means of determining infectious HIV-1-positive cells in blood samples.